Dans les marges du monde, des tribus sahariennes mondialisées. Réseaux commerciaux, réseaux tribaux et connexions politiques mondialisés depuis l’Ouest saharien - Ali Bensaâd (L’Année du Maghreb)
From the Saharan margins of Maghreb, on the sidelines even in breach of the formal frameworks of trade, huddled in tribal social structures, Moorish trade diasporas have spread into globalized networks who wove their fine scale webs through vast peripheral international spaces. From there, they have now taken over crossroads of international trade where they have built an economic influence vector of social and political influence whose effects are felt in both the country of origin and on the scene of international politics.